Application of Dental Pulp Stem Cells for Bone and Neural Tissue Regeneration in Oral and Maxillofacial Region - Yasuyuki Fujii; Ayano Hatori; Daichi Chikazu; Toru Ogasawara (Stem Cells International)
In the oral and maxillofacial region, the treatment of severe bone defects, caused by fractures, cancers, congenital abnormalities, etc., remains a great challenge. In addition, neurological disorders are frequently accompanied by these bone defects or the treatments for them. Therefore, novel bone regenerative techniques and methods to repair nerve injury are eagerly sought. Among them, strategies using dental pulp stem cells (DPSCs) are promising options. Human DPSCs can be collected easily from extracted teeth and are now considered a type of mesenchymal stem cell with higher clonogenic and proliferative potential. DPSCs have been getting attention as a cell source for bone and nerve regeneration. In this article, we reviewed the latest studies on osteogenic or neural differentiation of DPSCs as well as bone or neural regeneration methods using DPSCs and discussed the potential of DPSCs for bone and nerve tissue regeneration.